Dominasi dalam Hubungan Sosial Tokoh pada Novel Naomi Karya Tanizaki Junichiro: Analisis Konflik Otoritas Perspektif Ralf Dahrendorf - Fina Pramesta; Anas Ahmadi; Moh. Ahsan Shohifur Rizal (Educational Journal, 2026)
Literary works, as representations of social reality, often portray dynamics of power relations, domination, and resistance within society. The novel Naomi by Tanizaki Junichiro is one such work that illustrates authority conflict in social relationships between characters, particularly between Joji and Naomi. This study aims to describe the forms of domination and resistance in their relationship and to explain the resulting shifts in the structure of power. This research employs a qualitative method using Ralf Dahrendorf’s theory of authority conflict as its analytical framework. The data source is the Indonesian translated version of the novel Naomi, collected through library research and a close reading-note-taking technique. The data are analyzed systematically through identification, classification, mapping, and interpretation based on the concepts of domination, subordination, resistance, and structural change. The findings reveal that initially Joji occupies a dominant position as the authority holder, while Naomi is in a subordinate position. However, as the story progresses, Naomi demonstrates various forms of resistance that eventually lead to a shift in the power structure. Ultimately, Naomi becomes the more dominant figure in the relationship. This study concludes that authority conflict not only generates tension but also drives structural changes in social relations.